2019
DOI: 10.1111/joor.12908
|View full text |Cite
|
Sign up to set email alerts
|

A methodology for evaluating tooth wear monitoring using timed automata modelling

Abstract: Objectives Tooth wear is a multifactorial condition leading to the loss of dental hard tissues. A counselling/monitoring protocol is of importance in order to keep that loss as limited as possible. Since many factors are involved and a time span of decades is included, research to disentangle all these processes in patients is difficult. Instead, a modelling technique was used that is able to deal with time, costs and probabilistic and stochastic information. The aim was to shed light on the question: does a y… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
1
0
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 7 publications
(2 citation statements)
references
References 26 publications
(68 reference statements)
0
1
0
1
Order By: Relevance
“…By doing this, the start of a restorative treatment can be postponed or even avoided. Recent research has revealed that yearly counselling/ monitoring is favourable towards counselling/ monitoring every five years 25 . It is beyond the scope of this article to discuss this in detail.…”
Section: Treatment/management Decisionsmentioning
confidence: 97%
“…By doing this, the start of a restorative treatment can be postponed or even avoided. Recent research has revealed that yearly counselling/ monitoring is favourable towards counselling/ monitoring every five years 25 . It is beyond the scope of this article to discuss this in detail.…”
Section: Treatment/management Decisionsmentioning
confidence: 97%
“…Це наштовхнуло на думку про необхідність дослідити стан оклюзійних співвідношень у період адаптації пацієнтів до відновлювальних зубних конструкцій. Результати досліджень свідчать, що оскільки передчасні контакти у більшості випадків не зникають, необхідна додаткова курація пацієнтів в період адаптації (1-6 місяць) до незнімних протезів з метою стабілізації оклюзійних співвідношень [2,7]. Загально встановлено, що середня кількість оклюзійних контактів знаходиться у безпосередній залежності від безперервності зубних рядів та терміну виготовлення ортопедичних конструкцій [8].…”
Section: постановка проблемиunclassified